Isaac, Iphigeneia, Ignatius : martyrdom and human sacrifice - Pesthy-Simon, Monika, 1954- (New York : Central European University Press, 2017)
What is the meaning of the martyr's sacrifice? Is it true that the martyr imitates Christ? After the "one and eternal" sacrifice of Jesus, why are the occasional new (and often quite numerous) sacrifices necessary? What is the underlying divinitical concept behind these acts? How do these ideas survive in present times? The author considers martyrdom as a voluntary human sacrifice. The two emblematic figures of this transformation are Iphigeneia and Isaac. Pesthy argues that all the peoples in the environment in which Christianity came into being are characterized by an ambiguous and often hypocritical attitude toward human sacrifice: in theory they condemn it as barbarian and belonging to bygone times, in other cases they accept, admire and practice it. In modern Christianity, martyrs are real sacrifices, not symbolical ones. Our feelings about martyrs vary: we may admire their unbending courage and heroism or be irritated by their stubbornness, or even feel disgusted at the fanaticism with which they strove for death. Whatever our feelings may be, we must acknowledge that a very strong motivation is necessary to accept voluntarily or even seek death.
Human sacrifice in the Old Testament -- Greece, Rome and Carthage -- Early Judaism -- The death of Jesus -- The martyr's sacrifice : case studies -- The models of the martyr -- The meaning of the martyr's sacrifice -- Epilogue : the developments of martyrology after Constantine.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Martyrdom -- Christianity; Voluntary human sacrifice; Martyrdom -- Christianity; Voluntary human sacrifice; RELIGION / Judaism / History; Electronic books